LEGAL PROTECTION AGAINST MINORITY SHAREHOLDERS FOR THE IMPLEMENTATION OF A GENERAL MEETING OF SHAREHOLDERS (GMS) THAT EXPUSED TIME - Yatny Nur Afrianty; Wira Franciska (Research Parks Publishers, 2021)
The General Meeting of Shareholders (GMS) must be held no later than 6 (six) months after the financial year ends (Article 78 Paragraph 2 of The Company Law). When a company does not hold an annual GMS on a regular basis it can cause legal problems and cause losses to shareholders, especially minority shareholders, minority shareholders can not find out information on the company's conditions, company financial reports, etc. related to the company. The problem that became the discussion in this study was how to protect the law for minority shareholders for the implementation of the GMS that went beyond the period and how the legal consequences for the company. The method used in this study is a normative juridical approach which emphasizes the legal literature source, namely legislation. The specifications of this study are in the research with descriptive analysis. The data collected in this thesis comes from books on law, especially relating and Limited Liability Companies, minority shareholders and Limited Liability Company Laws. The theory used in this thesis is the theory of legal protection and the theory of legal certainty. The study results show that in the Law Number 40 year 2007 concerning Limited Liability Companies, there was little protection for minority shareholders if there was a delay in the implementation of the GMS, because there were no sanctions of any kind, so that it did not cause nay legal consequences for the company, although it can be said that if no GMS is implemented, the responsibility of the company has not been completed in that year. However, there are efforts that can be made by minority shareholders, namely by filling a lawsuit / or request to the head of the district court to obtain a determination to hold a GMS